A Framework for Modeling Rock Glaciers and Permafrost at the Basin‐Scale in High Alpine Catchments - Pruessner, Luisa; id_orcid:0 000-0001-8125-2426; Huss, Matthias; Phillips, Marcia; Farinotti, Daniel; id_orcid:0 000-0003-3417-4570 (American Geophysical Union, 2021)
Since rock glaciers are believed to be more resilient to climate change, water stores therein may become important water reservoirs in future, in particular in dry regions, which currently rely on glacial runoff. In order to estimate and evaluate the future runoff potential from permafrost and rock glaciers, distributed runoff models suitable for high Alpine catchments are needed. An extension to the distributed Glacier Evolution and Runoff Model (GERM) to include permafrost and rock glaciers in Alpine catchments is presented here, and compared to the established one dimensional (1D) physics‐based model SNOWPACK. The new permafrost component introduced to GERM treats permafrost as discreet depth layers in a 1D column for all grid cells, which have bulk thermal properties calculated from their constituents (ice, water, air, and solid component). The temperature evolution is computed using heat conduction and latent heat exchanges, modified by ventilation effects. Finally, we infer water runoff from permafrost degradation. Ground temperature variations calculated by both models are compared to borehole measurements at three Alpine sites and similar performances are found. Differences between the models are present in the amplitude of seasonal ground temperature variations, with SNOWPACK having a tendency to slightly overestimate them, while GERM underestimates them. ISSN:1942-2466